Assessing the Financial Performance of Technology Sector Firms in Indonesia - Aniqotunnafiah Aniqotunnafiah; Elmi Rakhma Aalin; Anisa Kusumawardani (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2025)
This study examines the effect of Liquidity (Quick Ratio), Solvency (Debt to Asset Ratio), and Profitability (Return on Equity) on Financial Performance (Return on Assets) among technology sector companies in Indonesia during the 2021–2023 period. Using multiple linear regression analysis, the results show that Liquidity (QR) has a significant positive effect on financial performance, indicating that higher liquidity enhances a firm’s ability to meet short-term obligations and improve profitability. Solvency (DAR) has a negative and significant effect on financial performance, suggesting that excessive debt usage weakens a firm’s profitability. Meanwhile, Profitability (ROE) shows a positive and significant influence on Return on Assets (ROA), implying that efficient use of equity contributes to better financial outcomes. Simultaneously, Liquidity, Solvency, and Profitability significantly affect financial performance, with the model explaining 71.7% of the variance in ROA. These findings highlight the importance of maintaining optimal liquidity, balanced capital structure, and efficient equity utilization to enhance corporate financial performance